Lymph node transplantation for the treatment of lymphedema. Issue 5 (21st August 2018) - Gould, Daniel J; Mehrara, Babak J; Neligan, Peter; Cheng, Ming‐Huei; Patel, Ketan M
Abstract : Lymphedema is a complex disease process with deranged lymphatic transport, fluid accumulation and secondary lipedema and fibrosis. This is a challenging disease to treat with a surgical focus on debulking and physiologic strategies. One strategy is the use of vascularized lymph node transplant (VLNT) to improve physiologic lymph clearance. In this article, VLNT is discussed in detail, including mechanisms, combined strategies, and outcomes.